PENGELOLAAN LINGKUNGAN BELAJAR BERBASIS TRI HITA KARANA DI TK EKA DHARMA SEBAGAI UPAYA PENGINTEGRASIAN PENDIDIKAN LINGKUNGAN - I Gd. Arya Wiradnyana (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2020)
Tackling environmental damage is not solely the responsibility of the government, but also educational institutions. Educational institutions must be able to facilitate the formation of students to become future successors of the nation who are able to apply the principles of sustainability and ethics in the environment from an early age. One of the policies that have been taken by the government to overcome these problems is environmental education. To be able to integrate environmental education in kindergarten, proper management of indoor and outdoor learning environments is needed. One model of education that can be applied to integrate environmental education in kindergarten is through education oriented to the values ??of Tri Hita Karana (THK). Based on these problems, this research was conducted with the aim to describe the management of a learning environment based on Tri Hita Karana in Eka Dharma Kindergarten as an effort to integrate environmental education. This research is classified as qualitative research with data collection methods such as observation, interviews, and questionnaires. The results of this study indicate that the management model of indoor and outdoor learning environments which are oriented towards THK values ??in Kindergarten Eka Dharma Singaraja can be applied to integrate environmental education. Through the THK concept which contains values ??such as: (1) nature conservation, (2) environmental preservation, (3) maintaining cleanliness, and (4) caring for plants can certainly foster student awareness in kindergarten about the importance of protecting the environment so that they can play an active role in environmental conservation and safety efforts.Keywords: Education, Environment, Tri Hita Karana